2014
DOI: 10.1002/jssc.201301138
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of cured tobacco using liquid chromatography with mass spectrometry: Method development and its application in investigating the chemical differences of tobacco from three growing regions

Abstract: Cured tobacco is an important plant material. Component studies are a big challenge for its significantly diverse chemical properties and vastly different concentrations. In this work, liquid chromatography with quadrupole time-of-flight mass spectrometry was used to perform a metabolomics study of cured tobacco owing to its efficient separation and detection of semipolar metabolites. A solvent of methanol/water (8:2, v/v) and 30 min of ultrasound time were found to be optimal to perform extraction. 95, 92, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Extreme temperature (together with water deficit) and high solar radiation were reported to strongly affect grapevine growth, which further led to negative effects on fruit and wine quality (Teixeira et al, 2014). A field study in China revealed that different field conditions also affected the profiles of polar metabolites in tobacco leaves such as flavonoids (Li et al, 2014). In 2 years of our field experiments, it rained only once during each year in India.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme temperature (together with water deficit) and high solar radiation were reported to strongly affect grapevine growth, which further led to negative effects on fruit and wine quality (Teixeira et al, 2014). A field study in China revealed that different field conditions also affected the profiles of polar metabolites in tobacco leaves such as flavonoids (Li et al, 2014). In 2 years of our field experiments, it rained only once during each year in India.…”
Section: Discussionmentioning
confidence: 99%
“…Plant metabolomics has been widely applied in comparing mutants and transgenic plants with their wild types, exploring the influence of external stimuli (such as processing) on chemical composition, controlling the quality of herbs and so on [6][7][8]. Up to now, discrimination of three different rhubarb products has been achieved based on HPLC-UV fingerprints [9].…”
Section: Introductionmentioning
confidence: 99%
“…To data LC-MS with reasonable qualitative and quantitative capability has been increasingly used for chemical profiling and QC of TCMs [6,10]. Among various LC platforms, ultra fast liquid chromatography (UFLC)…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has been used to determine quantitative differences of the endogenous metabolites to find the relationship between metabolites and its physiological or/and pathological changes . MS‐based analytical tools such as LC–MS , GC–MS , and CE–MS have been employed in metabolomic analysis, which produce a large amount of complex MS data. The effective biological conclusions will be obtained through the reliable processed MS data.…”
Section: Introductionmentioning
confidence: 99%